Alexis Retractor: Institutional Experience of Its Applications in Head and Neck Surgery and Review of the Literature. (May 2020) - Lee, Jasmine; Yu, Jason W.; Lee, Z-Hye; Levine, Jamie P.; Jacobson, Adam S.
Background: The Alexis retractor is a device that provides simultaneous radial retraction and wound protection during surgical procedures. Although typically used in abdominal and pelvic surgeries, there has been increased development of novel operative techniques utilizing the Alexis retractors in head and neck surgeries. Methods: We describe 2 cases of utilizing the Alexis retractor to attain transoral exposure in the setting of free flap reconstruction of intraoral defects. Results: In both cases, the Alexis retractor provided improved retraction, decreasing the number of instruments required for adequate exposure. Additionally, the polyurethane sheath component acted as a protective membrane over the lips and mucosa. Conclusions: The Alexis retractor can be a powerful retraction tool for certain surgical procedures involving the head and neck regions.